Ultrasonography of Cervical Lymph Nodes - Jagruti Kalola; Maulik Jethva; Raj Bhesdadiya (Asian Journal of Medical Radiological Research, 2020)
Background: Ultrasonography is a useful imaging tool in the evaluation of cervical lymph nodes. Gray-scale ultrasonography and color and power Doppler ultrasonography are commonly used in current practice.Aim: To determine the efficacy of ultrasound in differentiating between benign and metastatic group of cervical lymph nodes.Subjects and Methods: In this study, 160 patients age between 15 and 60 years with cervical lymphadenopathy referred for ultrasonography of neck to the Department of Radio diagnosis, P D U Medical College, over a period of 1 Year from December 2017 - December 2018 are included in this study. All scans carried out on high frequency linear transducer on Philips IU 22 ultrasound machine.Results: Lymph node with oval shape ([S/L] < 0.5) echogenic hilum, homogenous echotexture, and hilar vascularity were considered as signi?cant parameters in detecting non-neoplastic (reactive) lymph nodes, which showed matting with soft tissue edema. Nodes which were round shape (S/L ? 0.5), absent hilum, heterogeneous echotexture, hilar, capsular vessels, and mixed vascularity were considered as signi?cant parameters in detecting neoplastic (malignant) lymph nodes.Conclusion:The sonographic appearances of normal nodes differ from those of abnormal ones. Sonographic features that help to identify abnormal nodes include shape (round), absent hilum, intranodal necrosis, reticulation, calcification, matting, soft-tissue edema, and peripheral vascularity.